Into the wild … or not: Virtual nature experiences benefit well-being regardless of human-made structures in nature - Reese, Gerhard; Mehner, Marie; Nelke, Insa; Stahlberg, Jasmin; Menzel, Claudia (Frontiers in Virtual Reality, 2022)
Immersive nature experiences increase human well-being. There is now an increasing number of studies suggesting that virtual nature experiences – e.g., within a virtual reality (VR) environment – can evoke comparable benefits. In the current study using VR, we tested whether human-made structures within nature settings hinder such effects of virtual nature experience on well-being. To do so, 67 participants were led through a VR nature surrounding that was either wild and untouched by humans, or was characterized by few inconspicuous human structures (i.e., paths, buildings, walls, bridges). Before and after the intervention, we measured subjective vitality. After the intervention, we assessed perceived restorative outcome. Results revealed that both virtual nature experiences improved participants’ subjective vitality. Across both groups, participants reported relatively high - and similar - levels of restoration. These findings suggest that (virtual) nature experiences can be beneficial even when human-made structures interfere. Thus, irrespective of how pristine the environment is, the beneficial effects of immersive VR nature experiences provide opportunities for restoration when physical nature is inaccessible.